War-Induced Trade Shocks: A Statistical Analysis of Iraq-Ukraine Import-Export Dynamics in 2021 (Pre-War) and 2022 (Post-War) (Raparin Journal of Humanities (RJH), 2025)
This research aims to investigate the impact of the Russia-Ukrainian war on Iraq’s import-export dynamics with Ukraine. The study employs statistical tools such as the Wilcoxon rank test, Kolmogorov-Smirnov test, and Shapiro-Wilk test to analyze variations in trade quantities, providing robust insights into trade shocks caused by the conflict. Using data from both pre- and post-conflict periods, the study captures the fluctuating trade patterns between the two nations and examines the extent to which geopolitical instability can influence economic interactions. The analysis highlights a peak in Iraqi imports from Ukraine in mid-2021, followed by a sharp decline at the onset of the war in early 2022, with intermittent spikes in trade observed during the post-conflict phases. This demonstrates the war’s significant disruption to trade while emphasizing Iraq's economic resilience in navigating such challenges. The research contributes to a broader understanding of the implications of geopolitical conflicts on international trade, highlighting their destabilizing effects on supply chains and trade flows. Key recommendations for policymakers include the development of contingency strategies to mitigate the adverse effects of geopolitical instability on trade, the diversification of Iraq’s trading partners to reduce overdependence on specific regions, and the enhancement of internal economic resilience through targeted investment in non-oil sectors, particularly those that foster economic diversification and sustainable growth.